Efektivitas Berbagai Larutan Penyimpan terhadap Umur Simpan Hydrangea macrophylla: Effectivity of Several Holding Solutions on Hydrangea macrophylla’s Vase Life - Elke Camelia Halim; Suketi, Ketty; Krisantini; Muthi’ah Khairun Nisa (Jurnal Hortikultura Indonesia, 2022)
Hydrangea as cut flowers has a relatively shorter vase life compared to other flowers. One of the post harvest technologies to extend the vase life of Hydrangea flowers is by using holding solutions. This research was aimed to prolong the vase life of Hydrangea macrophylla using commercially available solutions (Chrysal and Floralife) and made up solution containing citric acid and sucrose. Postharvest treatment experiments were conducted in Leuwikopo 1-B Lecture Room, Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, using Hydrangea flowers obtained from a commercial garden in Ciloto, West Java. The experiment was set up in a completely randomised design (CRD) with holding solutions as a single factor, i.e. aquadest (P0), Chrysal (P1), Floralife (P2), and combination between 300 ppm citric acid and 3% sucrose (P3), with 5 replications, resulting in 20 experimental units.. Vase life observations were conducted daily and determined based on the duration until the flowers wilted. The result shows that solution containing 300 ppm citric acid and 3% sucrose has same effectivity as commercially available solutions, especially in vase life and flower color. Hydrangea flowers lasted up to 8.4 days on average and maintained their blue color until the end of the observation period. Key words: citric acid, cut flower, Hydrangea macrophylla, sucrose, vase life